LINGUISTIC CORPUS BASED ANALYSIS: COLLOCATION OF WORD MEANING “ACUTE” IN THE CORPUS COVID-19 - Rahmayani, Fitri Ana (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
This study presents a corporate-based analysis and aims to look for collocations that follow the word acute by using Word Sketch in the COVID-19 corpus through Sketch Engine software to find out what words follow the acute word and how it plays a role in using it. This study uses qualitative methods based on data collected through the Sketch Engine. It aims to find out the word acute based on its collection by taking data from the COVID-19 corpus. Data source from this research is acute word collocation through software from Sketch Engine. The stage for data collection is to enter the word acute in the concordance feature through the Sketch Engine software, then select the collocation icon and select span -3 + 3 (to the left -3 and to the right 3) so that the top 3 appear in the word of acute. The results obtained from this study are, side by side collocation of acute is respiratory, syndrome, and severe. In this case, the syndrome appeared as much as 19,938, respiratory appeared as much as 30,752, and severe appeared as much as 18,089. So, a more significant word that appears alongside the word acute is respiratory, which acts as a noun and its use to clarify the meaning of the SARS virus name.